Guidelines for the management of bacterial and fungal infections during chemotherapy for pediatric acute leukemia or solid tumors: what is available in 2010? - Elio Castagnola; Ilaria Caviglia; Riccardo Haupt (MDPI AG, 2011)
Optimizing the therapeutic strategies based on the results of randomized studies comparing different regimens led to a better prognosis of nearly all pediatric malignancies during the past four decades. Fever and neutropenia (FN) is a common complication in patients undergoing chemotherapy to treat cancer. There is no consensus on when standard therapy can be safely reduced; this lack of consensus leads to important variations in management of FN between different institutions, usually conducted according to local attitudes. To address this issue, the Infection working group of the Italian association for pediatric hematology oncology (AIEOP) organized a consensus meeting. This paper reports the agreement derived from this meeting.